Integration of mTOR and estrogen–ERK2 signaling in lymphangioleiomyomatosis pathogenesis - Gu, Xiaoxiao (National Academy of Sciences, 2013)
Lymphangioleiomyomatosis (LAM) is a destructive lung disease of women associated with the metastasis of tuberin-null cells with hyperactive mammalian target of rapamycin complex 1 (mTORC1) activity. Clinical trials with the mTORC1 inhibitor rapamycin have revealed partial efficacy but are not curative. Pregnancy appears to exacerbate LAM, suggesting that estrogen (E(2)) may play a role in the unique features of LAM. Using a LAM patient-derived cell line (bearing biallelic Tuberin inactivation), we demonstrate that E(2) stimulates a robust and biphasic activation of ERK2 and transcription of the late response-gene Fra1 associated with epithelial-to-mesenchymal transition. In a carefully orchestrated collaboration, activated mTORC1/S6K1 signaling enhances the efficiency of Fra1 translation of Fra1 mRNA transcribed by the E(2)–ERK2 pathway, through the phosphorylation of the S6K1-dependent eukaryotic translation initiation factor 4B. Our results indicate that targeting the E(2)–ERK pathway in combination with the mTORC1 pathway may be an effective combination therapy for LAM.